(untitled) - Trần, Viết Hoàn (Hà Nội, 2010)
Ghi lại một số chuyện kể về ngày sinh của Bác và thư, điện của Người cảm ơn đồng bào nhân ngày sinh
Keywords: Ho Chi Minh,Communists,Người cộng sản,Hồ Chí Minh; Biography,Tiểu sử; Vietnam,Việt Nam